Nasal Base Narrowing of the Caucasian Nose Through the Cerclage Technique - Mocellin, Marcos; Pasinato, Rogerio; Berger, Cezar Augusto Sarraff; Soares, Caio Márcio Correia; Grinfeld, Arthur; Fagundes, Marina Serrato Coelho (Arquivos Internacionais de Otorrinolaringologia, 2010)
Introduction: Several techniques can be performed to reduce the nasal base (narrowing), as skin resection vestibular columellar skin resection, resection of skin in elliptical lip narinary, sloughing of skin and advancements (VY technique of Bernstein) and the use of cerclage sutures in the nasal base.Objective: To evaluate the technique of cerclage performed in the nasal base, through endonasal rhinoplasty without delivery of basic technique, in the Caucasian nose, reducing the distance inter-alar flare and correcting the wing with consequent improvement in nasal harmony in the whole face.Methods: A retrospective analysis by analysis of clinical documents and photos of 43 patients in whom cerclage was made of the nasal base by resecting skin ellipse in the region of the vestibule and the nasal base (modified technique of Weir) using colorless mononylon® 4 “0” with a straight cutting needle. The study was conducted in 2008 and 2009 at Hospital of Paraná Institute of Otolaryngology - IPO in Curitiba, Parana - Brazil. Patients had a follow up ranging 7-12 months.Results: In 100% of cases was achieved an improvement in nasal harmony, by decreasing the inter-alar distance.Conclusion: The encircling with minimal resection of vestibular skin and the nasal base is an effective method for the narrowing of the nasal base in the Caucasian nose, with predictable results and easy to perform.
Keywords: rhinoplasty; suture techniques; vestibuloplasty